Strategi Badan Wakaf Indonesia (BWI) dalam Penyelesaian Sengketa Wakaf di Aceh Indonesia - Fatiya, Ina; Umuri, Khairil; Riyaldi, Muhammad Haris; Nurlina, Eka; Muftahuddin, Muftahuddin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the dispute resolution strategies implemented by the Indonesian Waqf Board (Badan Wakaf Indonesia-BWI)Representative Office in Aceh and to assess their compliance with Islamic legal principles. The urgency of this study stems from the high potential for waqf disputes in Aceh, primarily due to incomplete administrative documentation and inadequate records of waqf assets. These conditions often trigger disputes between nazhir, wakif, and heirs, thereby requiring an effective, structured, and sharia-compliant dispute resolution mechanism. This research employs a descriptive qualitative approach using document analysis and in-depth interviews with informants from BWI Aceh and academic experts. The data were analyzed thematically to identify patterns of dispute resolution and their relevance to the concepts of shulh and tahkim in Islamic law. The findings indicate that BWI Aceh prioritizes non-litigation mechanisms through mediation and arbitration. Mediation serves as the primary instrument, conducted through problem identification, facilitated dialogue, and negotiation until a mutually acceptable settlement is reached. Arbitration is applied when mediation does not produce an agreement. This approach aligns with Islamic values that emphasize deliberation, justice, and peace. These strategies have proven effective in resolving various types of disputes, including conflicts involving overlapping claims and differing interpretations of management rights. The study concludes that BWI Aceh’s strategy is consistent with Islamic legal principles and contributes to enhancing legal certainty and protecting waqf assets. Nevertheless, strengthening data management, disseminating regulations, and improving nazhir capacity remain necessary to ensure more optimal waqf dispute resolution.